The autotransporter BafA contributes to the proangiogenic potential of Bartonella elizabethae. (15th March 2023) - Suzuki, Natsumi; Kumadaki, Kayo; Tatematsu, Kaoru; Doi, Yohei; Tsukamoto, Kentaro
Abstract: Bartonella elizabethae is a rat‐borne zoonotic bacterium that causes human infectious endocarditis or neuroretinitis. Recently, a case of bacillary angiomatosis (BA) resulting from this organism was reported, leading to speculation that B. elizabethae may also trigger vasoproliferation. However, there are no reports of B. elizabethae promoting human vascular endothelial cell (EC) proliferation or angiogenesis, and to date, the effects of this bacterium on ECs are unknown. We recently identified a proangiogenic autotransporter, BafA, secreted from B. henselae and B. quintana, which are recognized as Bartonella spp. responsible for BA in humans. Here, we hypothesized that B. elizabethae also harbored a functional bafA gene and examined the proangiogenic activity of recombinant B. elizabethae –derived BafA. The bafA gene of B. elizabethae, which was found to share a 51.1% amino acid sequence identity with BafA of B. henselae and 52.5% with that of B. quintana in the passenger domain, was located in a syntenic region of the genome. The recombinant protein of the N‐terminal passenger domain of B. elizabethae ‐BafA facilitated EC proliferation and capillary structure formation. Furthermore, it upregulated the receptor signaling pathway of vascular endothelial growth factor, as observed in B. henselae ‐BafA. Taken together, B. elizabethae –derived BafA stimulates human EC proliferation and may contribute to the proangiogenic potential of this bacterium. So far, functional bafA genes have been found in all BA‐causing Bartonella spp., supporting the key role BafA may play in BA pathogenesis.